Assisting hand use and self‐care bimanual performance of children with unilateral spastic cerebral palsy. (22nd July 2022) - Brandão, Marina B.; Coster, Wendy J.; Figueiredo, Priscilla R. P.; Amaral, Maíra F.; Gordon, Andrew M.; Mancini, Marisa C.
Abstract: Aim: To examine the relationship between assisting hand use in bimanual activities and children's self‐care activities and task performance. Method: We retrospectively analysed daily functioning (Pediatric Evaluation of Disability Inventory [PEDI]) and bimanual performance (Assisting Hand Assessment [AHA]) data from the assessment of 112 children (mean age: 8 years 10 months [SD 2 years 1 month], range 3 years 7 months–17 years 4 months; 66 males, 46 females) with unilateral spastic cerebral palsy (CP). We used Rasch analysis to examine the relationship between individual item scores from the AHA and the self‐care items (functional skills, caregiver assistance) from the PEDI. Results: Most self‐care functional skills and caregiver‐assisted tasks were located on the middle of the unidimensional continuum. These items showed similar levels of difficulty as the items from the AHA related to the effective coordination of two hands, appropriate pace, and use of the assisting hand to stabilize and release objects, as well as variations in arm movements. Interpretation: The distribution of the PEDI self‐care and AHA items along the unidimensional continuum illustrates the relationship between assisting hand use and self‐care bimanual performance. Interpretation of the items' locations on the hierarchical unidimensional continuum may be helpful to therapists' clinical reasoning and suggest intervention goals to improve the hand function and daily functioning of children with unilateral spastic CP. Such an application needs further investigation. Abstract : Portuguese translation of this Original Article is available in the online issue.